Indonesia’s Gastrodiplomacy in a Constructivist Framework: A Form of National Identity Strengthening (JURNAL DURA NEGARA, 2026)
This study analyzes Indonesia’s gastrodiplomacy within a constructivist framework as a form of strengthening national identity at the global level. Departing from the limitations of realist and liberal approaches that tend to place food as a secondary instrument in international politics, this research argues that cuisine is a meaningful social medium capable of shaping perceptions and identity through cross-cultural interactions. Using a literature review method, the study examines academic publications and official policy documents, particularly the Indonesia Spice Up the World (ISUTW) program as the main case. The findings show that Indonesia’s gastrodiplomacy functions not only as a soft power instrument to increase spice exports and expand the network of Indonesian restaurants abroad, but also as a constructive practice that reproduces Indonesia’s historical narrative as a spice nation. Through interactions between state and non-state actors—including the diaspora, culinary entrepreneurs, media, and international communities—food becomes a symbol that communicates the values of hospitality, diversity, and creativity. Thus, gastrodiplomacy contributes to nation branding while simultaneously building Indonesia’s identity in a dialogical manner within the international arena.
Keywords: gastrodiplomacy; constructivism; national identity; soft power